On One Property of a Regular Markov Chain - Ibragimov, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We prove that if a certain row of the transition probability matrix of a regular Markov chain is subtracted from the other rows of this matrix and then this row and the corresponding column are deleted, then the spectral radius of the matrix thus obtained is less than 1. We use this property of a regular Markov chain for the construction of an iterative process for the solution of the Howard system of equations, which appears in the course of investigation of controlled Markov chains with single ergodic class and, possibly, transient states.